Bodies/Countries:: Mary Melfi’s “Flirt” with Feminism in Infertility Rites - Karpinski, Eva (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
Mary Melfi's Infertility Rites can be seen as a record of one woman's struggle for control of her body, both in a social and biological sense; it is a struggle she is bound to lose as long as she treats her body as an enemy rather than an ally. Nina's sense of herself as a woman is determined by her ethnic background, where "Canadianness" rubs against "Italianness," as well as by other dichotomies around which her life is structured such as work/home, public/private, motherhood/infertility, sexism/political correctness, immigrant/mainstream or patriarchal/feminist. Nina's increasingly essentialized sense of femininity is projected in the novel as the function of her ethnicity. Her gradual fall into her own body seems to her like a retreat into a new country that is at war with itself. Melfi's metafictional novel, like Nina's subjectivity, is invaded and traversed by many contending discourses. Melfi's insertion of "studies" - brief notes based on statistical data and scientific research - is an important structural device that enhances the novel's focus on female subjectivity as animated by contradictions.